2009
DOI: 10.1007/s12185-009-0306-5
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil combined with tacrolimus and minidose methotrexate after unrelated donor bone marrow transplantation with reduced-intensity conditioning

Abstract: We evaluated the efficacy of a post-grafting immunosuppressive regimen consisting of tacrolimus, methotrexate, and mycophenolate mofetil (MMF) in 21 adults (median age, 55 years) with poor-risk hematologic malignancy who underwent unrelated bone marrow transplantation after fludarabine-based reduced-intensity conditioning (RIC). In combination with intravenous tacrolimus and minidose methotrexate (5 mg/m2 on days 1, 3, and 6), MMF was orally administered at 30 mg/kg daily in three divided doses between days 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Patients with malignant hematologic neoplasms received myeloablative or fludarabine-based reduced-intensity conditioning regimens with or without total-body irradiation (TBI) as described elsewhere [27,28]. Patients with aplastic anemia received conditioning regimens consisting of high-dose cyclophosphamide and horse or rabbit antilymphocyte globulin with or without 2-4 Gy TBI.…”
Section: Transplantation Proceduresmentioning
confidence: 99%
“…Patients with malignant hematologic neoplasms received myeloablative or fludarabine-based reduced-intensity conditioning regimens with or without total-body irradiation (TBI) as described elsewhere [27,28]. Patients with aplastic anemia received conditioning regimens consisting of high-dose cyclophosphamide and horse or rabbit antilymphocyte globulin with or without 2-4 Gy TBI.…”
Section: Transplantation Proceduresmentioning
confidence: 99%
“…In RIST using ATG, alemtuzumab, or TBI, the reported incidence of acute GVHD was 19-47% [1][2][3][4][5][6][7], 16-36% [5,[8][9][10], and 3-77% [11][12][13][14][15][16][17][18], respectively. In RIST with TBI, the incidence of acute GVHD tended to be higher than in RIST with T-cell depletion.…”
Section: Discussionmentioning
confidence: 99%
“…These patients included eleven individuals with acute myeloid leukemia, nine with acute lymphoblastic leukemia (ALL) (including seven Ph-positive ALL), two with refractory anemia with excess blasts II [RAEB II, a variant of myelodysplastic syndrome (MDS)], six with non-Hodgkin's lymphoma, and three with the lymphomatous type of adult T-cell leukemia/lymphoma. All patients had experienced chemotherapy prior to transplantation with a median of six courses of prior chemotherapy (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Reduced-intensity conditioning was chosen because of age above 50 years (n = 17), cardiac dysfunction (n = 7), prior allogeneic hematopoietic stem cell transplantation (n = 4), prior intense chemotherapy (n = 2), or the patient's choice (n = 1).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three retrospective studies [49][50][51] suggested the safety and efficacy of MMF together with Tac or CsA as GVHD prophylaxis. Wakahashi et al [51] reported that the blood concentration of MMF at 2 h after the start of infusion could be a surrogate marker of the area under the curve and helpful for predicting acute GVHD development.…”
Section: Mycophenolate Mofetil (Mmf)mentioning
confidence: 99%